Trichophyton verrucosum infection in livestock in the Chitral district of Pakistan - Khalid Hameed; Farhana Riaz Ch; Muhammad Ali Nawaz; Syed Muhammad Saqlan Naqvi; Yvonne Gräser; Christiane Kupsch; Mario Pasquetti; Luca Rossi; Anna Rita Molinar Min; Paolo Tizzani; Elisa Chiavassa; Andrea Peano (Journal of Infection in Developing Countries)
Introduction: Trichophyton verrucosum belongs to the dermatophyte fungi, closely related organisms that cause skin infections in animals and humans. T. verrucosum infection has been reported in livestock and people in different countries from all continents. Human cases have been reported in different areas of Pakistan, but there is little information about the animal source of the fungus. Methodology: Dermatological specimens collected in the Chitral district of Pakistan for a study on mange in livestock were retrospectively analyzed for the presence of T. verrucosum. In total, 5,873 animals (1,087 cows, 2,033 goats, and 2,753 sheep) were screened for evidence of dermatological lesions during two surveys performed in the summer and winter seasons. Skin scrapings collected from animals with lesions were analyzed by direct microscopic examination after digestion in sodium hydroxide and a real-time polymerase chain reaction (PCR) targeting pathogenic Trichophyton species. Results: At microscopy, samples from 18 cows (1.6%), 3 sheep (0.1%), and 4 goats (0.2%) were positive for fungal elements consistent with T. verrucosum. PCR confirmed the microscopy results. The prevalence was lower than that reported in other countries in intensive breeding farms. Results agree with the literature regarding factors affecting T. verrucosum diffusion, i.e., infection was more prevalent in cattle, especially in younger animals during the winter season. Conclusions: This study reports, for the first time, the presence of T. verrucosum in livestock in Pakistan. A better knowledge of the animal role in the spread of this fungus may allow the adoption of more efficient control measures and prophylaxis.